(Chiro)optical Properties of π-Extended Spiro-Double Carbo[7]helicene - Kumar, Viksit; Dongre, Sangram D.; Vandhanam, Aparna; Jadhav, Ashok Badrinarayan; Kumar, Jatish; Babu, Sukumaran Santhosh (Journal of Physical Chemistry Letters, 2025)
Helical nanographenes are a fascinating class of pi-extended chiral nanocarbons, where structural helicity imparts intrinsic chirality and unique optoelectronic properties to the rigid carbon framework. In this work, we synthesized a hexa-peri-hexabenzocoronene-based pi-extended spiro-double carbo[7]helicene. The helical distortion of the structure was unambiguously confirmed by X-ray crystallography. The optical properties were explored through UV-Vis absorption, fluorescence, and phosphorescence measurements, complemented by density functional theory (DFT) calculations. Remarkably, the pi-extended spiro-double carbo[7]helicene exhibited thermally activated delayed fluorescence (TADF) at room temperature and phosphorescence at low temperatures. Chiral HPLC successfully resolved the enantiomers into three fractions: (PP), (MM), and the meso forms (PM)/(MP), and chiroptical studies of the pure enantiomers revealed a moderately high g lum value of 1.58 x 10-3. Finally, the origin of the observed dissymmetry factors was rationalized by analyzing the transition electric dipole moments (TEDM) and transition magnetic dipole moments (TMDM) derived from time-dependent density functional theory (TD-DFT) calculations.